DEVELOPMENT OF FINE MOTOR SKILL OF THE CHILDREN THROUGH SCISSORING ACTIVITIES IN PERTIWI 1 DUKUH WALUH KINDERGARTEN - Siti Nurjanah; Fauzi (PG PAUD Universitas Negeri Surabaya, 2025)
This study aimed to improve children's fine motor skills through task-based learning in scissor-cutting activities at TK Pertiwi 1 Dukuhwaluh, Kembaran District, using a Classroom Action Research approach with observational data collection. The participants were 15 children aged 5-6 years in Group B, and the data were analyzed quantitatively. In the pre-cycle, 13% of children (2 students) had not yet developed the skills, 73% (11 students) were beginning to develop, 7% (1 student) were developing as expected, and 7% (1 student) had very well-developed skills. By Cycle 1, no children remained in the undeveloped category, while the beginning to develop group maintained 73% (11 students) with some individual changes, and both the developing as expected and very well-developed groups increased to 13% (2 students each). In Cycle 2, all children showed progress, with no students in the beginning stage, 13% (2 students) maintaining expected development, and a significant 87% (13 students) achieving very well-developed status. The study exceeded its 80% success target, with 87% of children reaching the highest skill level, demonstrating that the task-based cutting activities effectively enhanced fine motor skills in Group B children at TK Pertiwi 1 Dukuhwaluh.